Foreign policy theories, actors, cases - Smith, Steve 1952-; Hadfield, Amelia 1975-; Dunne, Timothy 1965-; Kitchen, Nicholas (Oxford University Press, 2024)
This ground-breaking text provides the ideal introduction to the ever-changing field of foreign policy. With a unique combination of theories, actors and cases in a single volume, the expert contributors provide students with a valuable and accessible introduction to what foreign policy is and how it is conducted.With an emphasis throughout on grounding theory in empirical examples, the textbook features a section dedicated to relevant and topical case studies where foreign policy analysis approaches and theories are applied. The expert team of contributors clearly conveys the connection between international relations theory, political science, and the development of foreign policy analysis, emphasizing the key debates in the academic community. New to this edition- New chapters on postcolonialism and gender support the growing inclusion of these topics in foreign policy teaching.- Foreign policy case study chapters in part three are fully revised with more systematic focus on Asia, and major revisions to the chapters on China, India, and Brazil to reflect contemporary discourse.- New chapter on aid diplomacy.- Available to all users of the e-book and Politics Trove, online resources have been fully updated and new multiple-choice questions for students added.Digital formats and resourcesThe fourth edition is available for students and institutions to purchase in a variety of formats, and is supported by online resources.- The e-book offers a mobile experience and convenient access along with functionality tools, navigation features, and links that offer extra learning support: www.oxfordtextbooks.co.uk/ebooks- Additional online resources include self-test questions for students, PowerPoint slides for lecturers, and a timeline updated to show the latest key foreign policy events